Penerapan Pembelajaran Berbasis Praktik Dalam Inovasi Kue Engkhui Sebagai Upaya Pelestarian Kudapan Tradisional Aceh - Juwairiah, Juwairiah; Fitri, Yurda; Reza, Muhammad; Khairiah; Nur Rahmy, Illya; Fahrizal, Aril (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study aimed to preserve the traditional Acehnese snack, Engkhui cake, through the implementation of practice-based learning in Islamic boarding schools. The research objectives were: (1) to implement practice-based learning as a medium to introduce and preserve the Engkhui cake, (2) to develop innovative flavor variants without altering the original recipe, and (3) to enhance the students’ awareness and involvement in preserving local culture. The study employed a qualitative descriptive approach with a participatory model, which was conducted at Nurul Ulum Islamic Boarding School, Peureulak, East Aceh, involving 20 students. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the interactive model of Miles and Huberman. The findings emphasized that the practice-based learning approach in education not only enriched the students’ learning experience but also supported cultural preservation within the boarding school environment.